The business of economics - Kay, J. A. (New York: Oxford University Press, 1996)
Kay's overall purpose is to show that economics can and should be brought to the analysis of business problems. In doing so he distinguishes his approach from that of the forecasters and the formula-bound, and those on the other hand who suggest abandoning economics in our postmodern complex world
Includes Index.
Keywords: Business Law; Political Economy; United Kingdom of Great Britain and Northern Ireland Companies